2016
DOI: 10.1108/nlw-10-2015-0078
|View full text |Cite
|
Sign up to set email alerts
|

Information literacy in Nigerian universities trends, challenges and opportunities

Abstract: Purpose The purpose of this study was to determine the information literacy trends, challenges and opportunities in Nigerian universities, With focus on its characteristics; content and adequacy for students’ information literacy development and lifelong learning. The effort to ensure that university students are empowered to acquire the competences needed for all round education and lifelong learning has been the primary focus of the university curriculum. University regulatory body in Nigeria emphasised the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…In Dubicki’s (2013) study, several faculty members mentioned that academic integrity needs to be discussed with students regarding referencing borrowed ideas and citing sources used in research, including specific format requirements. The study by Anunobi and Ukwoma (2016) reported that citation interpretation and investigating authors’ expertise were not part of the content of the programmes in 60 per cent of the universities studied.…”
Section: Undergraduates’ Knowledge Of Citation and Referencing Stylesmentioning
confidence: 98%
See 1 more Smart Citation
“…In Dubicki’s (2013) study, several faculty members mentioned that academic integrity needs to be discussed with students regarding referencing borrowed ideas and citing sources used in research, including specific format requirements. The study by Anunobi and Ukwoma (2016) reported that citation interpretation and investigating authors’ expertise were not part of the content of the programmes in 60 per cent of the universities studied.…”
Section: Undergraduates’ Knowledge Of Citation and Referencing Stylesmentioning
confidence: 98%
“…It should be noted, however, that Michalak and Rysavy (2016) in their study found that students tend to overate their information literacy skills. Previous study by Anunobi and Ukwoma (2016) found that the key areas of information literacy namely: problem identification, development of research Assessment of information literacy skills strategy, and information synthesis were lacking in many of the Nigerian university programmes.…”
Section: Evaluating Online Information and Sourcesmentioning
confidence: 99%
“…For many years, libraries have been conducting library orientation or user education, essentially designed to acquaint new students with the available library resources and to enable them to explore effectively the existing knowledge base and ameliorate their information search skills (Anunobi and Ukwoma, 2016). In many universities, this has been the mere introduction of students to collections and services, with the primary aim of transferring the skills that would enable the library users to identify, select, locate and retrieve the relevant information resources and make the users appreciate the library as the top source of inquiry, by using the collection effectively (Idiodi, 2005).…”
Section: Background Literaturementioning
confidence: 99%
“…Swapna and Biradar (2017) argued that while the concept of information literacy has been embraced by many universities, it is important that initiatives are effectively promoted and executed to produce more confident and independent information seekers. Anunobi and Ukwoma (2016), in their study on information literacy in Nigerian universities, posited that the underdevelopment of information literacy programs in higher education institutions can be attributed to the attitude of key stakeholders including administrators, academics, students and libraries. They noted additionally, "the lack of essential management commitment, ignorance of what information literacy stands for, the willingness of various departments to collaborate for effective development of programs, aversion, to innovative curricula and inadequate technological infrastructure as a hindrance to the growth of effective information literacy programs."…”
Section: Information Literacy Instructionmentioning
confidence: 99%